2021
DOI: 10.1111/ijn.12997
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression and social support across pregnancy in women with a history of recurrent miscarriage: A prospective study

Abstract: Aim: Women with a history of recurrent miscarriage are a vulnerable population. This study aimed to examine changes and relationships among anxiety, depression and social support across three trimesters of pregnancy in women with a history of recurrent miscarriage.Methods: A prospective, longitudinal study was employed. A convenience sample of 166 pregnant women with a history of recurrent miscarriage completed the measures at their 6-12, 20-24 and 32-36 gestational weeks.Results: The prevalence of anxiety at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
13
0
2
Order By: Relevance
“…Sample sizes varied from 54 participants in a follow-up of a previous randomized trial [ 51 ] to 12,386 couples in a study with findings on both maternal and paternal depression [ 53 ]. Most of the included studies [ 38 41 , 43 , 44 , 47 , 50 , 51 , 58 60 , 62 , 63 , 68 ] in the mid or late pregnancy, four [ 45 , 54 56 ] started in early pregnancy, and ten studies [ 42 , 46 , 48 , 49 , 53 , 61 , 64 , 65 , 67 , 70 ] started after birth. Women were on average aged between 18 and 40 years old.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample sizes varied from 54 participants in a follow-up of a previous randomized trial [ 51 ] to 12,386 couples in a study with findings on both maternal and paternal depression [ 53 ]. Most of the included studies [ 38 41 , 43 , 44 , 47 , 50 , 51 , 58 60 , 62 , 63 , 68 ] in the mid or late pregnancy, four [ 45 , 54 56 ] started in early pregnancy, and ten studies [ 42 , 46 , 48 , 49 , 53 , 61 , 64 , 65 , 67 , 70 ] started after birth. Women were on average aged between 18 and 40 years old.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we found that women with lower social support and higher self-reported adherence to the Traditional Female Role were at the highest risk of experiencing postpartum depressive symptoms [ 38 ]. A study conducted in China found that anxiety and depression are highly prevalent in pregnant women who have experienced recurrent miscarriages, particularly in the early weeks of pregnancy when social support is at its lowest level [ 56 ]. These findings converge with those from the past studies that identified social support as an important buffer against anxiety and depression throughout the pregnancy [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 In Guangzhou, China, the incidence rate of anxiety in early-stage, middle-stage and late-stage pregnancy was 47.6%, 36.1% and 32.5%, respectively, whereas the incidence of depression was 38%, 34.3% and 31.3%, respectively. 35 While in central London, of the recurrent miscarriage women, 34% fulfilled the criteria for post-traumatic stress symptoms at first month, 26% at third month and 21% at ninth month, respectively, and that of anxiety was 30% at first month, 25% at third month and 22% at ninth month, as well as depression for 10% at first month, 8% at third month and 7% at ninth month, respectively. 36 Since the psychological incidence rate is common after pregnancy loss, available screening tools and treatment programs for psychological health consequences of miscarriage need to be accessible.…”
Section: Miscarriagementioning
confidence: 98%
“…64,65 Psychosocial stress theory believes that social support is a protective element against anxiety and depression during pregnancy. 35,66,67 Patient-centered counseling, including decision satisfaction and shared decisionmaking, has a positive influence on psychological consequences for women seeking pregnancy termination. 68 Besides, providing counseling based on health promotion awareness can decrease psychological health problems and increase self-esteem.…”
Section: Interventionsmentioning
confidence: 99%